Effect of acceptance and commitment therapy for adolescent depression: a meta-analysis - Yu, Xin; Zhao, Bing; Yin, Tongtong; Qu, Haiying; Zhang, Jingxuan; Cheng, Xiaojing; Chen, Xu (Frontiers in Psychiatry, 2025)
ObjectivesThis study conducted a systematic review of published randomized controlled trials (RCTs) to evaluate the efficacy of acceptance and commitment therapy (ACT) for adolescent depression, while also examining its pertinent characteristics.MethodsWe conducted systematic searches of electronic databases in accordance with PRISMA guidelines to ensure rigorous screening, data extraction, and quality assessment. Additionally, we employed random-effects models and performed subgroup analyses.ResultsA meta-analysis of 25 studies with 2,352 participants showed that ACT significantly reduced depressive symptoms in adolescents. Improvements in psychological flexibility significantly predicted reductions in depression. Subgroup analysis revealed that, at post-test, ACT was significantly more effective than wait-list controls in reducing depressive symptoms, though it was not superior to Treatment As Usual or active treatment groups. Furthermore, offline ACT was significantly more effective than Internet-based ACT in reducing depressive symptoms. Comparisons of intervention settings also indicated that ACT was more effective in group settings than individual ones. However, no significant difference was found between clinical and non-clinical samples.ConclusionsThe current study suggests that ACT effectively reduces depressive symptoms, with psychological flexibility playing a crucial role in this improvement. Intervention forms and sample types should be considered when implementing ACT interventions. Extensive research is still needed for further exploration.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023494677, identifier CRD42023494677.